Workplace violence: issues in threat management - Holbrook, Christina M. (Routledge, 2019)
Preface -- Introduction: what is workplace violence? -- The foundation : creation of a workplace violence prevention policy -- Development of a threat management program -- Principles of threat assessment and management -- Legal considerations in the management of threats -- By michael a. crane, esq. and matthew w. doherty -- The employee assistance program (eap) and it's role in managing workplace threats -- Risk assessment in domestic violence and stalking cases -- By pamela a. paziotopolous -- Case studies -- Research in assessing levels of threat : implications for workplace training